Distinctive Regulation of Carbapenem Susceptibility in Pseudomonas aeruginosa by Hfq - Sonnleitner, Elisabeth; Pusic, Petra; Wolfinger, Michael T.; Bläsi, Udo (Frontiers in Microbiology, 2020)
Carbapenems are often the antibiotics of choice to combat life threatening infections caused by the opportunistic human pathogen Pseudomonas aeruginosa. The outer membrane porins OprD and OpdP serve as entry ports for carbapenems. Here, we report that the RNA chaperone Hfq governs post-transcriptional regulation of the oprD and opdP genes in a distinctive manner. Hfq together with the recently described small regulatory RNAs (sRNAs) ErsA and Sr0161 is shown to mediate translational repression of oprD, whereas opdP appears not to be regulated by sRNAs. At variance, our data indicate that opdP is translationally repressed by a regulatory complex consisting of Hfq and the catabolite repression protein Crc, an assembly known to be key to carbon catabolite repression in P. aeruginosa. The regulatory RNA CrcZ, which is up-regulated during growth of P. aeruginosa on less preferred carbon sources, is known to sequester Hfq, which relieves Hfq-mediated translational repression of genes. The differential carbapenem susceptibility during growth on different carbon sources can thus be understood in light of Hfq-dependent oprD/opdP regulation and of the antagonizing function of the CrcZ RNA on Hfq regulatory complexes.